Microporous Metal-Organic Frameworks for Adsorptive Separation of C5-C6 Alkane Isomers - Wang, Hao; Li, Jing (Accounts of chemical research, 2019)
The separation of alkane isomers, particularly C5-C6 alkanes, is of paramount importance in the petrochemical industry to achieve high quality gasoline. Upon catalytic isomerization reactions, less branched alkanes (with lower octane number) need to be separated from their more branched isomers (with higher octane number) in order to improve the octane rating of gasoline. To reduce the high energy input associated with distillations, the primary separation technique currently used in industry, adsorptive separation by porous solids has been proposed. For example, zeolite 5A has been used as the adsorbent material for adsorptive separation of linear alkanes from their branched isomers, as a supplement technology to distillations. However, due to the limited number of zeolite structures and the lack of porosity tenability in these compounds, the task has not been fully fulfilled by using zeolites. Metal-organic frameworks (MOFs), in light of their structural diversity and high tunability in terms of surface area, pore size, and pore shape, offer new opportunities for resolving industrially relevant separation of alkanes through selective adsorption. This Account summarizes recent development of microporous MOFs for the separation of alkanes, with an emphasis on C5-C6 alkane isomers, including early examples of alkane separation by MOFs, as well as the latest advancement on tailor-made microporous MOFs for size sieving of C5-C6 alkane isomers. The limitation of zeolite 5A as a sorbent material for the separation of C5-C6 alkane isomers lies in its relatively low adsorption capacity. In addition, it is not capable of separating branched alkanes, which is a crucial step for further improving the octane rating of gasoline. The high porosity and tunable pore size and pore shape of MOFs may afford them higher adsorption capacity and selectivity when used for alkane separation. MOFs with pore size slightly larger than the kinetic diameter of branched alkanes can effectively separate alkane isomers through thermodynamically controlled separation, as seen in the case of Fe (bdp) (bdp = 1,4-benzenedipyrazolate). This MOF is capable of separating a mixture of hexane isomers by the degrees of branching, with higher adsorption capacity than zeolites under similar conditions but with relatively low selectivity. One effective strategy for obtaining MOFs with optimal pore size and pore shape for highly selective adsorption is to make use of reticular chemistry and precise ligand design. By applying topologically directed design strategy and precisely controlling the pore structure or ligand functionality, we have successfully synthesized a series of highly robust MOFs built on tetratopic carboxylate linkers that demonstrate high performance for the separation of C5-C6 alkane isomers. Zr-bptc (bptc = 3,3',5,5'-biphenyltetracarboxylate) adsorbs linear alkanes only and excludes all branched isomers. This size-exclusion mechanism is very similar to that of zeolite 5A. Yet, Zr-bptc has a significantly enhanced adsorption capacity for -hexane, 70% higher than that of zeolite 5A under identical conditions. Zr-abtc (abtc = 3,3',5,5'-azobenzenetetracarboxylate) is capable of discriminating all three C6 alkane isomers via a thermodynamically controlled process, yielding a high separation factor for monobranched over dibranched isomers. MOFs with flexible framework may exhibit unexpected but desired adsorption properties. Ca(H tcpb) (tcpb = 1,2,4,5-tetrakis(4-carboxyphenyl)-benzene) can fully separate binary or ternary mixtures of C5-C6 alkane isomers into pure form through selective molecular sieving as a result of its temperature- and adsorbate-dependent framework flexibility. The intriguing structural properties and exceptional tunability of these MOFs make them promising candidates for industrial implementation of adsorptive separation of alkane isomers.